Some chemical composition and biological activity of northern Argentine propolis - Isla, Maria Ines (2005)
Twenty-five samples of propolis were collected from seven different regions in northern Argentina; ethanolic extracts of propolis were prepared from all samples, and the respective samples were examined for UV absorption spectra, RPHPTLC, RPHPLC, antimicrobial activity, antiradical activity, and total phenolic content. It was found that 16 of the 25 samples showed a phenolic profile similar to that found in samples from southern Brazil and corresponding to poplar-based propolis and that the rest of the samples showed a different profile and higher antimicrobial and antiradical activities.